2011
DOI: 10.1074/jbc.m111.221648
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of a Genetically Encoded Dark-to-Bright Reporter for Caspase Activity

Abstract: Fluorescent proteins have revolutionized modern biology with their ability to report the presence of tagged proteins in living systems. Although several fluorescent proteins have been described in which the excitation and emission properties can be modulated by external triggers, no fluorescent proteins have been described that can be activated from a silent dark state to a bright fluorescent state directly by the activity of an enzyme. We have developed a version of GFP in which fluorescence is completely que… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
85
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 59 publications
(85 citation statements)
references
References 39 publications
0
85
0
Order By: Relevance
“…We have previously shown that the appendage of the 27-amino acid quenching peptide causes CA-GFP to oligomerize into a mixed population that is predominantly tetramer and higher order oligomers. 1 We hypothesize that this oligomerization is at the root of the CA-GFP quenching mechanism. To fully harness the potential of CA-GFP for other uses, it is essential to understand the structural basis of the immature chromophore at a mechanistic level.…”
Section: Resultsmentioning
confidence: 93%
See 4 more Smart Citations
“…We have previously shown that the appendage of the 27-amino acid quenching peptide causes CA-GFP to oligomerize into a mixed population that is predominantly tetramer and higher order oligomers. 1 We hypothesize that this oligomerization is at the root of the CA-GFP quenching mechanism. To fully harness the potential of CA-GFP for other uses, it is essential to understand the structural basis of the immature chromophore at a mechanistic level.…”
Section: Resultsmentioning
confidence: 93%
“…13,14 Despite the fact that all 11 strands must be available for proper folding of GFP, it is possible to cut GFP following the 10th strand to make split GFP. 4 In the split-GFP system, co-expression of GFP strands 1-10 (GFP [1][2][3][4][5][6][7][8][9][10] ) with the 11th strand allows reassociation of the 11th strand with GFP [1][2][3][4][5][6][7][8][9][10] and folding of the GFP b-barrel. Once the full GFP b-barrel is formed the chromophore is competent to mature, and split GFP becomes fluorescent.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations